Single canal in a single-rooted mandibular second molar: An enigma - Sonu Acharya (Wolters Kluwer Medknow Publications, 2016)
The case report here tries to describe the variation of root canal anatomy in a second mandibular molar, which is rare in occurrence in literature. This case report presents a relatively rare case of mandibular second molar with single root and a single root canal in a 45-year-old female patient who had come to dental clinic with a complain of pain in the left lower tooth region. Ambiguity in the canal morphology of the second molar is quite common. Knowledge of variations in internal anatomy of teeth is important for success in endodontic treatment. Root canal morphology is limitless in its variability and clinicians must be aware that anatomic variations constitute a formidable challenge to endodontic success. Hence, clinicians have to take utmost care when these cases with single canal and single root come to clinic.